Aspects regarding Burnout syndrome in healthcare workers with secondary education in the Republic of Moldova, during the pandemic period - PODOROGHIN, Marina; PALADI, Adriana (One Health & Risk Management, 2023)
Introduction. The COVID-19 pandemic has created favorable conditions for the onset and exacerbation of burnout syndrome. The aim of the research was to assess the degree of impact of burnout syndrome on mid-level medical staff during the pandemic period, as well as its determinants.Material and methods. The research was based on a selective descriptive, quantitative study conducted from November 2022 to March 2023. The quantitative component involved surveying a sample of 463 nurses and midwives involved in providing medical care to COVID-19 positive patients.Results. The results indicate that burnout syndrome during the pandemic period affected 100% of mid-level medical personnel who provided medical care to COVID-19 patients. The most pronounced dimension of burnout syndrome was psycho-emotional exhaustion, at 29.2%. Younger age and shorter work experience were more affected among mid-level medical personnel. Medical staff in republican, departmental, and municipal medical institutions were more affected than those in district institutions.Conclusions. Burnout syndrome was detected in all medical workers involved in healthcare delivery, predominantly manifesting itself through psycho-emotional exhaustion, with varying degrees of intensity among different categories of medical personnel.